The Effectiveness of Liraglutide in Nonalcoholic Fatty Liver Disease Patients with Type 2 Diabetes Mellitus Compared to Sitagliptin and Pioglitazone. (13th August 2012) - Ohki, Takamasa; Isogawa, Akihiro; Iwamoto, Masahiko; Ohsugi, Mitsuru; Yoshida, Haruhiko; Toda, Nobuo; Tagawa, Kazumi; Omata, Masao; Koike, Kazuhiko
Abstract : Background . Liraglutide leading to improve not only glycaemic control but also liver inflammation in non-alcoholic fatty liver disease (NAFLD) patients. Aims . The aim of this study is to elucidate the effectiveness of liraglutide in NAFLD patients with type 2 diabetes mellitus (T2DM) compared to sitagliptin and pioglitazone. Methods . We retrospectively enrolled 82 Japanese NAFLD patients with T2DM and divided into three groups (liraglutide: N = 26, sitagliptin; N = 36, pioglitazone; N = 20). We compared the baseline characteristics, changes of laboratory data and body weight. Results . At the end of follow-up, ALT, fast blood glucose, and HbA1c level significantly improved among the three groups. AST to platelet ratio significantly decreased in liraglutide group and pioglitazone group. The body weight significantly decreased in liraglutide group (81.8 kg to 78.0 kg, P < 0.01 ). On the other hands, the body weight significantly increased in pioglitazone group and did not change in sitagliptin group. Multivariate regression analysis indicated that administration of liraglutide as an independent factor of body weight reduction for more than 5% (OR 9.04; 95% CI 1.12–73.1, P = 0.04 ). Conclusions . Administration of liraglutide improved T2DM but also improvement of liver inflammation, alteration of liver fibrosis, and reduction of body weight.